Analisis Populasi dan Sebaran Rusa Timor (Rusa timorensis) di Taman Wisata Alam Pulau Rusa, Kecamatan Pantar Barat Laut, Kabupaten Alor, Provinsi Nusa Tenggara Timur - Karel Febryanto Buling; Maria M. E. Purnama; Fadlan Pramatana (Wana Lestari, 2023)
Timor deer (Rusa timorensis) is a type of tropical deer originating from Java, which has a fairly wide distribution in Indonesia. Rusa Island is one of the areas in Alor Regency which has a fairly large forest area and can provide a source of food or animal needs so that it becomes a habitat for Timor deer. This study aims to determine the level of population density and distribution of the Timor deer (Rusa timorensis) in the Rusa Island Nature Park. The data collection method used in this research is the concentration count method. Observations were made at a point as a place for animal encounters, then along the observation point the number of deer individuals found was recorded with 2 times of observation, namely morning and afternoon. The data obtained were analyzed using the formula for density or abundance, sex ratio, analysis of vegetation and distribution. The results showed that the number of Timor deer population encounters at the Pulau Rusa TWA was 26 with 11 males and 15 females with a density of 1.17 tails/ha. In terms of sex ratio, the population structure of the deer shows that the ratio of male and female deer is balanced because there are more female deer than males. The distribution of Timor deer (Rusa timorensis) in the area is influenced by vegetation and TWA. Deer Island has a savanna habitat type and several types of plants that can be used as shelter.